Hepatic stellate cells express thymosin Beta 4 in chronically damaged liver. - Jieun Kim; Sihyung Wang; Jeongeun Hyun; Steve S Choi; Heejae Cha; Meesun Ock; Youngmi Jung (PLoS ONE, 2015)
Although the various biological roles of thymosin β4 (Tβ4) have been studied widely, the effect of Tβ4 and Tβ4-expressing cells in the liver remains unclear. Therefore, we investigated the expression and function of Tβ4 in chronically damaged livers. CCl4 was injected into male mice to induce a model of chronic liver disease. Mice were sacrificed at 6 and 10 weeks after CCl4 treatment, and the livers were collected for biochemical analysis. The activated LX-2, human hepatic stellate cell (HSC) line, were transfected with Tβ4-specific siRNA and activation markers of HSCs were examined. Compared to HepG2, higher expression of Tβ4 in RNA and protein levels was detected in the activated LX-2. In addition, Tβ4 was up-regulated in human liver with advanced liver fibrosis. The expression of Tβ4 increased during mouse HSC activation. Tβ4 was also up-regulated and Tβ4-positive cells were co-localized with α-smooth muscle actin (α-SMA) in the livers of CCl4-treated mice, whereas such cells were rarely detected in the livers of corn-oil treated mice. The suppression of Tβ4 in LX-2 cells by siRNA induced the down-regulation of HSC activation-related genes, tgf-β, α-sma, collagen, and vimentin, and up-regulation of HSC inactivation markers, ppar-γ and gfap. Immunofluorescent staining detected rare co-expressing cells with Tβ4 and α-SMA in Tβ4 siRNA-transfected cells. In addition, cytoplasmic lipid droplets were observed in Tβ4 siRNA-treated cells. These results demonstrate that activated HSCs expressed Tβ4 in chronically damaged livers, and this endogenous expression of Tβ4 influenced HSC activation, indicating that Tβ4 might contribute to liver fibrosis by regulating HSC activation.